Sprache und Kommunikation im technischen Zeitalter : Wieviel Internet (v)erträgt unsere Gesellschaft? - Marx, Konstanze; Schwarz-Friesel, Monika (Age of Access? Grundfragen der Informationsgesellschaft., 2013)
The Internet has not only transformed our verbal communication but has also changed all methods of recording, transmitting, and managing information. The subject of this volume is the interaction between technological development and communicative practice, as well as its socio-cognitive dynamics. This anthology, which contains contributions by experts in the fields of social psychology, communication studies, and linguistics, undertakes a critical discussion of interaction in the age of technology. In doing so, it makes an important contribution to scientific discourse about processes of conv.